Bioethics, a transversal theme for secondary education, a study in teachers - Basagni, Daniela; González-García, Francisco (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper describes the data provided by 40 secondary education teachers on their knowledge and teaching in bioethics issues. The textbook, debate and research in small groups are the usual tools. Their training needs and the most appropriate methodology for teaching are discussed. Human health, biotechnology and new topics, such as animal abuse, are the most commented among students, without appreciating gender differences. Bioethics can be considered as a transversal one that encourages interdisciplinary work and the acquisition of skills.